Circadian rhythm disturbance in agitation of Alzheimer's disease: Neuropsychiatry and behavioral neurology/Assessment/Measurement of neuropsychiatric/Behavioral and psychological symptoms. (7th December 2020) - Rosenberg, Paul B.; Wu, Mark N.; Spira, Adam P.; Wanigatunga, Sarah K.; Zipunnikov, Vadim; Outen, John D.
Abstract: Background: Agitation in Alzheimer's disease (AD) is a major cause of distress and burden for AD caregivers and may be driven by disrupted circadian rhythms (often termed "sundowning") and sleep. In healthy individuals, the circadian clock that generates these rhythms controls patterns in mood, wakefulness, and alertness. We examined the association of activity and sleep with agitation in AD in an observational study using wrist actigraphy, home sleep testing, and measurement of core body temperature. Method: We studied 13 participants with AD+agitation (AgitAD+) and 7 with AD but without agitation (AgitAD‐) who completed wrist actigraphy for one week (to quantify rest/activity rhythms and sleep); consumed an ingestible, disposable temperature sensor for 1‐2 days (to quantify core body temperature, a marker of the endogenous circadian rhythm); and completed a single night of home sleep testing (HST) using NoxT3. Agitation was measured with the Neuropsychiatric Inventory‐Clinician Version (NPI‐C). Result: 20 participants have completed to date (7 controls/13 agitated, mean age of 68 years, 60% female, 10% African American). There were no statistically significant differences observed in actigraphy‐derived sleep parameters between agitated and non‐agitated participants (2‐group t‐test; see Table 1). However, significant differences between the groups have been observed in the rest/activity rhythms: compared to participants without agitation (AgitAD‐), AgitAD+ participants had lower amplitude in the morning and greater amplitude in the afternoon and evening (Figure 1). We also have performed function‐on‐scalar regression (FOSR) (Goldsmith et al., 2015, Biometrics 71:344‐353) using subject‐specific activity profiles as outcomes and age and Agitation/Controls status as scalar predictors. Figure 2 shows functional effects of age on Rest/Activity Rhythm (left panel) and the functional effect of Agitation status (right panel), the red background shows the pointwise statistically significant (p<0.05) times of the day. Adjusted for age, Agitation was associated with a lower amplitude in the morning period and a trend towards larger amplitude in the afternoon and evening period (not statistically significant). Conclusion: The collection of multimodal noninvasive data on sleep, activity, and core body temperature is feasible in agitated AD outpatients. We will present HST and core body temperature data at AAIC. Funding: R01AG054771.